Impact Of Training On Employee Satisfaction And Change Management: A Pragmatic Study With Special Reference To Employees Working In Luxury Hotels Of Mumbai (PUSA Journal of Hospitality and Applied Sciences, 2022)
Background: It was always a challenge for hotel industry to find and retain skilled manpower  and most of the hotels depend on in-house training programme to train and develop the  employees as per their requirement. It is easy for hotels to retain staff if they are well-trained,  they enjoy their work and are satisfied with workplace. COVID-19 pandemic presented  one more challenge to hotel industry i.e., to embrace changes as per the expectations  of market. Objectives: The main objectives of the study were to find out the impact of  training towards employee satisfaction and change management. To establish the influence  of employee satisfaction towards change management. Methodology: The factors shortlisted  towards employee satisfaction were rewards, nature of work, supervision, benefits, work environment and co-workers. Factors identified for change management were strategic  success, technological changes, effective systematic plan, communication, environment for  change and change management. The research design for this paper was descriptive. The  study was conducted for employee working in four major revenue producing operational  departments. Total 16 hotels of city of Mumbai were approached for data collection. Due  diligence was taken to collect data from different demographic profiles such as ownership  pattern of hotels, department and experience of employees, their qualifications etc. Total  165 samples were collected. Data was corroborated using Cronbach’s alpha and hypotheses  were validated using correlation and compare means one-way ANOVA tests with the help  of SPSS software. Result: Main findings of study were that nature of work and supervision  had moderate effect on work environment. Benefits, rewards and co-workers showed strong  correlation. Co-workers and work environment strongly impacted employee satisfaction.  Strategic success, environment for change and communication significantly affected change  management. Conclusion: Training was found to have significant relationship with employee  satisfaction and change management. Employee satisfaction had significant association with  change management. However technological change and effective systematic plan (factors of  change management) were not significantly associated.
Keywords: Hotel Industry; Employee Satisfaction; Change Management; Training